Pentingnya Pengetahuan yang Efektif dalam Meningkatkan Pengetahuan HIV/AIDS pada Remaja di SMA Bawakaraeng - Ricky. Z; Abd. Herman Syah Thalib; Rusli Rusli; Basmalah Harun; Sanghati Sanghati; Shaktya Arya Yuda; Nilma Israna (Pusat Riset dan Inovasi Nasional, 2022)
Human Immunodeficiency Virus (HIV) or Acquired Immune Deficiency Syndrome (AIDS) is a health problem that is quite complex and continues to increase in Indonesia. The number of HIV infections in Indonesia from 2005 to 2017 has reached 280,623. The highest percentage of AIDS cases is in the 20 – 29 year age group. Adolescents aged 15-24 years are a group that is vulnerable to HIV infection. The aim of PkM is that it is hoped that universities can participate in developing youth knowledge about HIV/AIDS at Bawakaraeng High School. Community service activities were carried out at Bawakareang High School on Thursday, April 20 2022 with 44 students participating using the counseling method. The results of the service had a positive impact on the participants in the pretest, there were 14 students (31.8%) who had good knowledge, and 26 (59.1%) who had sufficient knowledge, while 4 students (9.1%) had poor knowledge. This was followed by a 45 minute presentation of HIV/AIDS material and a 15 minute question and answer session. After that, the activity ended by working on posttest questions with the results showing that there was an increase in teenagers' knowledge, namely 36 students (82%) had good knowledge and 8 students (18%) had sufficient knowledge, while 0% had less knowledge. Further collaboration can be carried out by giving counseling to teenagers. which is on the same topic.